Transcriptional Control of Terminal Nephron Differentiation - El-Dahr, Samir S. (2008)
Terminal differentiation of epithelial cells into more specialized cell types is a critical step of organogenesis. Throughout the process of terminal differentiation, epithelial progenitors acquire or up-regulate expression of renal function genes and cease to proliferate, while expression of embryonic genes is repressed. This exquisite coordination of gene expression is accomplished by signaling networks and transcription factors which couple the external environment with the new functional demands of the cell. While there has been much progress in understanding the early steps involved in renal epithelial cell differentiation, a major gap remains in our knowledge of the factors that control the steps of terminal differentiation. A number of signaling molecules and transcription factors have been recently implicated in determining segmental nephron identity and functional differentiation. While some of these factors (the p53 gene family, HNF1β) promote the terminal epithelial differentiation fate, others (Notch, Brn-1, IRX, KLF4 and Foxi1) tend to regulate differentiation of specific nephron segments and individual cell types. This article summarizes current knowledge related to these transcription factors and discusses how diverse cellular signals are integrated to generate a transcriptional output during the process of terminal differentiation. Since these transcriptional processes are accompanied by profound changes in nuclear chromatin structure involving the genes responsible for creating and maintaining the differentiated cell phenotype, future studies should focus on identifying the nature of these epigenetic events and factors, how they are regulated temporally and spatially, and the chromatin environment they eventually reside in.